Eight Priorities for Improving Primary Care Access Management in Healthcare Organizations: Results of a Modified Delphi Stakeholder Panel - Rubenstein, Lisa (J Gen Intern Med, 2019)
OBJECTIVE: To identify priorities for improving healthcare organization management of patient access to primary care based on prior evidence and a stakeholder panel. BACKGROUND: Studies on healthcare access show its importance for ensuring population health. Few studies show how healthcare organizations can improve access. METHODS: We conducted a modified Delphi stakeholder panel anchored by a systematic review. Panelists (N = 20) represented diverse stakeholder groups including patients, providers, policy makers, purchasers, and payers of healthcare services, predominantly from the Veterans Health Administration. A pre-panel survey addressed over 80 aspects of healthcare organization management of access, including defining access management. Panelists discussed survey-based ratings during a 2-day in-person meeting and re-voted afterward. A second panel process focused on each final priority and developed recommendations and suggestions for implementation. RESULTS: The panel achieved consensus on definitions of optimal access and access management on eight urgent and important priorities for guiding access management improvement, and on 1–3 recommendations per priority. Each recommendation is supported by referenced, panel-approved suggestions for implementation. Priorities address two organizational structure targets (interdisciplinary primary care site leadership; clearly identified group practice management structure); four process improvements (patient telephone access management; contingency staffing; nurse management of demand through care coordination; proactive demand management by optimizing provider visit schedules), and two outcomes (quality of patients’ experiences of access; provider and staff morale). Recommendations and suggestions for implementation, including literature references, are summarized in a panelist-approved, ready-to-use tool. CONCLUSIONS: A stakeholder panel informed by a pre-panel systematic review identified eight action-oriented priorities for improving access and recommendations for implementing each priority. The resulting tool is suitable for guiding the VA and other integrated healthcare delivery organizations in assessing and initiating improvements in access management, and for supporting continued research. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-019-05541-2) contains supplementary material, which is available to authorized users.